Hawear As Customary Law In Protecting And Conserving Marine Resources In Southeast Maluku Regency - Labetubun, Muchtar Anshary Hamid; Angga, La Ode; Fataruba, Sabri (Technium Social Sciences Journal, 2021)
Protecting and conserving marine resources includes all marine ecosystems (both fauna and vegetation) in the sea and coastal areas that carry heredity traits, of which these species are part. The purpose of this study is to analyze the implementation of Hawear as customary law in protecting and preserving marine resources in Southeast Maluku Regency. This research method is a sociological legal research, carried out using an empirical juridical approach which is a qualitative analysis descriptive study. The results of the study show that the existence of the Hawear customary law is constitutionally recognized. Hawear’s customary law contains certain sanctions, the sanctions in Hawear’s customary law are not as severe as positive law or state law, but at least they can provide a deterrent effect from the customary side. So indigenous peoples who know and understand and obey customs and customary law, will definitely submit and obey customary law, namely the law of Hawear. The customary law of Hawear can be applied by indigenous peoples in the protection and preservation of the marine environment, so that it is not only the responsibility of the government, but also the responsibility of all levels of society, including the Indigenous Law Community